2012
DOI: 10.1155/2012/973041
|View full text |Cite
|
Sign up to set email alerts
|

A Dried Yeast Fermentate Prevents and Reduces Inflammation in Two Separate Experimental Immune Models

Abstract: Diverse and significant benefits against cold/flu symptoms and seasonal allergies have been observed with a dried fermentate (DF) derived from Saccharomyces cerevisiae (EpiCor) in multiple published randomized trials. To determine if DF may influence other immune conditions, two separate animal studies were conducted. Study 1 examined the ability of DF to prevent or reduce inflammation when given orally for 14 days to rats prior to receiving 1% carrageenan (localized inflammation model). DF significantly (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Previous work has also demonstrated the anti-inflammatory effects of this dried fermentate in animal models. 16 Recent work has documented that the dried fermentate retains anti-inflammatory properties after in vitro digestion, as shown by the reduction in interleukin-8 and tumor necrosis factor-alpha production by Caco-2/THP-1 cocultures exposed to the dried fermentate from the dynamic gastrointestinal simulator SHIME Ò . 18 In the SHIME model, the dried fermentate also showed significant prebiotic potential, including modulation of the microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has also demonstrated the anti-inflammatory effects of this dried fermentate in animal models. 16 Recent work has documented that the dried fermentate retains anti-inflammatory properties after in vitro digestion, as shown by the reduction in interleukin-8 and tumor necrosis factor-alpha production by Caco-2/THP-1 cocultures exposed to the dried fermentate from the dynamic gastrointestinal simulator SHIME Ò . 18 In the SHIME model, the dried fermentate also showed significant prebiotic potential, including modulation of the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition to safety documentation, 15 evidence is accumulating to document other facets of the dried fermentate's bioactivities, pointing to more complex immune regulatory mechanisms of action, including anti-inflammatory effects. 16 Other aspects associated with the dried fermentate consumption include beneficial effects on gut health. 17,18 The aim of this study was to expand the understanding of the anti-inflammatory properties of this dried yeast fermentate by documenting specific effects on controlled inflammatory insults in vitro and in vivo.…”
Section: Introduction Imentioning
confidence: 99%
“…The scouring in calves increased when the weaning process started; however, SCFP-supplemented calves seemed to be less affected during this period compared with CON. Research in mice and nursery piglets has shown that SCFP can modulate the immune system in the weaning period (Shen et al, 2009;Evans et al, 2012). Further research could help elucidate the mechanisms by which SCFP can reduce diarrhea during weaning.…”
Section: Calf Healthmentioning
confidence: 99%
“…Further, layers shed less Salmonella which effectively reduces the reservoir potential of eggs (Possemiers et al, 2013). This barrier function is further protected by an increased production of non-specific innate proteins, such as lysozymes and IgM (Evans et al, 2012;Jensen et al, 2007;Jensen et al, 2011;Possemiers et al, 2013). Within the innate immune system, phagocytes show more active immunophenotypes (Chou et al, 2017;Jensen et al, 2007;Possemiers et al, 2013).…”
Section: Xpc and Its Production Benefitsmentioning
confidence: 99%
“…Within the innate immune system, phagocytes show more active immunophenotypes (Chou et al, 2017;Jensen et al, 2007;Possemiers et al, 2013). There is also an increase in the production of chemokines and cytokines that assist in recruiting and activating effector cells to clear the invading pathogen (Evans et al, 2012;Jensen et al, 2007;Jensen et al, 2011;Possemiers et al, 2013).…”
Section: Xpc and Its Production Benefitsmentioning
confidence: 99%